Climate change impact on high latitude freshwater fish populations - Smalås, Aslak (UiT The Arctic University of Norway, 2021)
Climate change is one of the greatest threats to animal wildlife in high latitude freshwater ecosystems. Climate warming is rapidly increasing water temperatures in these areas, affecting biological processes of ectotherms such as growth, maturation and reproduction, which in turn trigger population responses. The magnitude of the effects of climate warming will vary depending on the thermal niche and phenotype of species. Climate change will continue to redistribute species, and fish species from warmer temperature guilds will invade and possibly take over areas where cold water fish currently dominate. Hence, it is important to establish the performance of cold vs warmer water species in a warming Arctic. The aim of this thesis is therefore to provide novel insights and predictions on population level implications of climate change for both cold- and cool water fish at high latitudes. The primary focus is on climate effects mediated by direct and indirect individual-level responses to increasing water temperatures, addressed using long-term empirical investigations and modelling in retrospective and prospective studies. In addition, the thesis addresses interactions between climate change and size-selective harvesting, a main pressure on high latitude fish populations, by modelling their cumulative effects to evaluate risks and reveal potential synergistic threats. The thesis documents how both cold- and cool water fish at their northern range edge have increased their somatic growth rates during the last three decades of warming. However, the cool-water adapted vendace and perch displayed a higher increase in juvenile somatic growth with warming compared to cold-water Arctic charr and whitefish, stressing how the thermal niche modulates the magnitude of warming effects. The individual based models developed for this thesis predict a further increase in somatic growth towards year 2100 under warming scenarios (RCP-4.5, -8.5), with cool water fish displaying a greater increase in somatic growth rate than cold ...